(أسباب الطلاق وآثاره عند المجتمع في قرية سونجكار (دراسة حالة في قرية سونجكار مويو الشمالية سومباوا نوسا تينجارا الغربية - Mu’jizat Al Marwa; Mulyono Mulyono; Abdul Basith (Universitas Muhammadiyah Surabaya, 2020)
ABSTRACT The increasing number of population every year, the number of divorces increases. It was like what happened in Songkar Village. Songkar Village is part of the jurisdiction of the Sumbawa Besar Religious Court. The number of divorce cases in the Sumbawa Besar Religious Court in 2017 reached 705 cases in the Sumbawa Regency. In 2018, divorce cases increased to reach 818 cases. There has been an increase of 113 cases in one year.Therefore, researchers formulated two problems: What are the causes of divorce in the Songkar Village community ?, and what are the cousequences of divorce in the Songkar Village community ?.This study uses qualitative research methods with a case study approach in the field to examine the natural conditions of objects with data collection techniques through interviews, observation, and documentation.The results of this study indicate that the causes of divorce in Songkar Village include infidelity, interference from the family of a married couple, one of the parties leaving the spouse by becoming Indonesia labor, and the economy. As a result of divorce raises community concerns, especially to children, and gossip by the community.Keywords: Causes of Divorce, Consequences of Divorce, Songkar Society